Cultural Heritage Preservation Through Introduction of Indonesian Children's Songs at The Indonesian Republic School in Tokyo - Ghoni, Khoirul Abror Ad-Dluha; Avianto, Bhakti Nur; Ramadhina, Kaisyah Cika (Khidmatuna: Jurnal Pengabdian Masyarakat, 2024)
This community service research aims to introduce and preserve Indonesian culture among students at the Indonesian School in Tokyo (Sekolah Republik Indonesia Tokyo - SRIT) through the dissemination of traditional children's songs. The program, conducted from May 13 to 18, 2024, employed an interactive and structured approach. Activities included providing song guidebooks, introducing traditional musical instruments, and conducting group singing sessions. The results demonstrated that this approach successfully enhanced students’ understanding of Indonesian cultural identity, strengthened their sense of nationalism, and broadened their cultural awareness. Additionally, the program fostered character building and increased students’ appreciation for Indonesia’s cultural heritage. The initiative aligns with theories of character and arts education, as well as public policies supporting cultural preservation mandated by Law No. 5 of 2017 on Cultural Advancement. This program not only plays a vital role in maintaining cultural identity amidst globalization but also strengthens ties between the central government and its overseas representatives in cultural preservation efforts.